Chronic Kidney Disease Stage Is a Modulator on the Association between High-Sensitivity C-Reactive Protein and Coronary Vasospastic Angina - Heng-Jung Hsu; Chiung-Hui Yen; Kuang-Hung Hsu; I-Wen Wu; Chin-Chan Lee; Chiao-Yin Sun; Chia-Chi Chou; Chun-Yu Chen; Shih-Ying Yang; Chi-Jen Tsai; Mai-Szu Wu; Ming-Jui Hung (The Scientific World Journal)
The prevalence of coronary vasospasm and also the factors associated with coronary vasospasm in CKD is still unclear. In this cross-sectional study of 859 consecutive CKD patients with angina pectoris received coronary catheterization, we evaluated the factors associated with coronary vasospasm. Patients with vasospasm were older and had higher peripheral blood white cell counts, higher peripheral blood monocyte cell counts, higher haemoglobin levels, higher hs-CRP levels, and lower levels of serum creatinine than patients without vasospasm. The results of multivariate logistic regression analysis revealed that peripheral blood monocyte count and hs-CRP level were independently associated with coronary vasospasm in patients with stage 1 CKD. Only peripheral blood monocyte count but not hs-CRP was independently associated with coronary vasospasm in patients with stages 2 and 3 of CKD. In conclusion, peripheral blood monocyte count is independently associated with coronary vasospasm in patients with stage 1–3 CKD, whereas hs-CRP is only independently associated with coronary vasospasm in patients with stage 1 CKD.